Rectus Fascia Versus Fascia Lata for Autologous Fascial Pubovaginal Sling: A Single-Center Comparison of Perioperative and Functional Outcomes. Issue 11 (November 2020) - Peng, Michelle; Sussman, Rachael D.; Escobar, Christina; Palmerola, Ricardo; Pape, Dominique M.; Smilen, Scott S.; Rosenblum, Nirit; Brucker, Benjamin M.; Peyronnet, Benoit; Nitti, Victor W.
Abstract : (Abstracted from Female Pelvic Med Reconstr Surg 2020;26:493–497) Worldwide, there has been a decline in the use of synthetic slings due to mesh-related complications and litigation. This has led to increased interest in native tissue prolapse repair using pubovaginal slings.